Cladophialophora lanosa sp. nov., a New Species Isolated from Soil. Issue 2 (3rd April 2019) - Das, Kallol; Lee, Seung-Yeol; Jung, Hee-Young
Abstract: Cladophialophora is characterized by simple hyphomycetes with brown hyphae that give rise to branched chains of pale brown conidia and shows affinities with the Herpotrichiellaceae. A fungal strain belonging to the genus Cladophialophora was isolated from soil in Daegu, Korea. This strain produces numerous greenish to dark black lanose aerial mycelia with hair like structures. It is morphological similar to C . chaetospira, C . inabaensis, and C . multiseptata; however, the conidiophores and conidia sizes of the newly isolated strain (KNU16-032) are clearly different from them. The novelty of the strain was also confirmed based on phylogenetic analysis using the data sets of the internal transcribed spacer region of and the partial sequence of 28S ribosomal DNA region along with the cultural characteristics. Because morphological observations and phylogenetic analysis indicated that the strain is distinct from previously known Cladophialophora species, we propose this species as a new species Cladophialophora lanosa sp. nov., and provide the detailed descriptions in this study.